ALAN WALKER’S “LILY” SONG LYRICS TO DEPICT SATANIC TRICKS: A GENERIC STRUCTURE ANALYSIS AS RHETORIC - Idha Nurhamidah; Sugeng Purwanto; Diyah Fitri Wulandari (Universitas Bengkulu, 2021)
The current study investigated a song lyric entitled “Lily” in terms of its generic structure to come up with the rhetorical strategies—how satanic tricks influence people through human greed. Lily belongs to a lyric considered a narrative poem. It is theorized that a narrative poem is a poem or possibly a lyric which consists of orientation, complication and resolution. In other words, a lyric is structured as such to produce rhetorical strategies (goals) which were analyzed employing Aristotle’s ethos, logos and pathos. Meanwhile, in the complication analysis of Lily, not only did the study employ psychological theory but was also supported by social contexts to describe how satanic tricks were made use through human greed engineering in achieving the goal of negative thoughts generating. The findings indicate that human minds are in fact guided by both angels and satans. Angels guide any individual (Lily) to stay in track of the positive values while Satan whispers tricks to divert from the positive path toward the negative values by means of human greed. To confirm the findings, a survey was administered to 90 purposefully-selected teenagers in Semarang Municipality only to find that “Lily“ song lyrics failed to give any answer to the question whether or not she (Lily) can be saved despite her frequent calls for help.